Вихованці Глухівського учительського інституту М. Карпов та А. Михайлець за матеріалами Історико-педагогічного музею ГНПУ ім. О. Довженка - Крижанівський, В.М. (Сіверщина в історії України, 2020)
У статті опубліковано 12 документів про вихованців Глухівського учительського інституту М.О. Карпова та А.Є. Михайлеця, що зберігаються у фондах історико-педагогічного музею ГНПУ ім. О. Довженка. Запропоновані матеріали уможливлюють реконструкцію життєвого та творчого шляху випускників, що закінчили інститут у 19 08 та 1911 роках. Hlukhiv Teacher’s Institute was opened by Minister of Education
D. Tolstoi in 1874 in the former hetman’s capital. The Institute trained
teachers of city schools of Kyiv, Poltava, Chernihiv, Podolsk and Volyn
provinces, in 1874–1917 high school, women’s gymnasium. Many young
men wished to enter this school from the Ukrainian, Belarussian and
Russian regions of the Romanov Empire.
The Institute has graduated more than 800 students for the years 1874
- 1917. In the article we will publish 12 documents about M.O. Karpov
and A.Ye. Mikhalets. Karpov M.O. is our countryman from the village
Ulanovo, Hlukhiv district. He graduated from the Ulanovo and Hlukhiv
schools and Hlukhiv Teacher’s Institute (1908). Mykola Oleksandrovych
devoted half a century to teaching. He worked as a teacher of geography,
mathematics, Ukrainian language and literature in the city schools of
Uman, Talnoy, Kharkiv.
He submitted the documents (letters, biographical certificate) of the
life and professional path of the students (H. Illeiko, M. Moskalenko,
S. Kosmovych, I. Sukhorebrнi and others) to the Institute Historical and
Pedagogical Museum in 1966. The documents allow to reconstruct the
composition of the issue students in 1908, biographies of students, who
studied at the institute in the early twentieth century. M.O. Karpov submitted
a manuscript of memoirs about Hlukhiv in the Revolutionary period. The
manuscript has not been preserved in the museum’s holdings for 2020.
Mykhailets A.Ye. is another graduate, who graduated from the Hlukhiv
Teacher’s Institute in 1911. Avksentii Yevstafovych worked for 52 years as
a teacher of chemistry and science in the schools of Novozhybkov (Briansk
region, Russian Federation). He handed over important documents to the
museum’s holdings: informative recollections of the «Ukrainian Circle» by
Yevheii Vyrovyi, detailed recollections of the anti-religious strike of 1908,
the text of a celebratory performance in 1974.